Analysis of rotor vibration characteristics of surface mounted permanent magnet synchronous motor under air gap eccentricity fault - Rui Zhu; Tianzhen Jiang; Xin Tong; Qingpeng Han; Keyuan He; Siyu Xu; Mingxin Wang (Journal of Low Frequency Noise, Vibration and Active Control)
Taking a permanent magnet synchronous motor as the research object, the effect of air gap eccentricity fault on the vibration response characteristics of the motor rotor is analyzed through theoretical calculations, numerical simulation and finite element simulation. First, the change of air gap magnetic field under air gap eccentricity fault is analyzed, and then further calculated to obtain the unbalanced magnetic force under air gap fault by the expression of air gap magnetic field, at last, the rotor’s vibration response characteristics under the action of unbalanced electromagnetic force are obtained by the Newmark- β calculation method. Detailed analysis of the effects of eccentricity distance, eccentricity angle and motor pole-pair number on motor rotor vibration. Finally, the synchronous motor eccentricity fault model is built in ANSYS Maxwell electromagnetic simulation software, and the change characteristics of rotor unbalanced magnetic force after eccentricity fault are calculated and the results are consistent with the theoretical calculations.